Formulation and Comparative Bioavailability of 2 Ciprofloxacin Sustained Release Tablets - Zaid, A. N.; Qaddomi, A.; Khammash, S. (Arzneimittelforschung, 2012)
Background and the purpose of the study: The aim of this study is to formulate and evaluate the quality of ciprofloxacin (CAS number: 85721-33-1) sustained release tablet (Ciprocare®XR) 1 000 mg ciprofloxacin (test formulation) by comparing its pharmacokinetic parameters with Cipro®XR sustained release tablet (reference formulation). For this purpose ciprofloxacin SR tablets were developed using the 2-layer method. To assess the quality of the produced sustained release tablets a randomized, 2-way, crossover, bioequivalence study was performed in 24 healthy, male volunteers. The selected Middle Eastern volunteers were divided into 2 groups of 12 subjects. One group was treated with the reference formulation and the other one with the test formulation, with a cross-over after a drug washout period of 7 days. Blood samples were collected at fixed time intervals and Ciprofloxacin concentrations were determined by a validated HPLC assay method. The pharmacokinetic parameters AUC0–48, AUC0–∞, Cmax, Tmax, Ke and T1/2 were determined for both sustained release tablets and were compared statistically to evaluate the bioequivalence between the 2 formulations of ciprofloxacin, using the statistical model recommended by the FDA. The analysis of variance (ANOVA) did not show any significant difference between the 2 formulations and 90% confidence intervals (CI) fell within the acceptable range for bioequivalence. According to the obtained results it was concluded that the test and reference formulations are bioequivalent, since they exhibit comparable pharmacokinetic parameters.
Keywords: formulation; ciprofloxacin; bioequivalence; sustained release tablets